2020
DOI: 10.21203/rs.3.rs-110440/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Randomized Control Trial Study On The Effect Of Health Education In Promoting Adherence To Treatment Among The Urban And Rural Tuberculosis Patients In Kenya

Abstract: Background: Tuberculosis is a global health concern and the incident rate in Kenya remains high. Because of the long duration of standard treatment (six months), there is a risk of treatment default by patients. Low adherence to treatment may result in the emergence of resistant strains of the Mycobacterium Tuberculosis in turn increasing mortality and prolonging the treatment duration. The rising TB cases in Kenya have been associated with poor adherence and low cure rate arising from inappropriate health ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
2
0
0
Order By: Relevance
“…The outcome of the present study shows that the age of a patient does not determine their compliance to the treatment regimen, hence health education intervention should be targeted to all the patients in the referral hospital to ensure compliance. The finding corresponds with the observations of Mbuti et al 19 that reported no significant association between age and compliance to treatment regimen after post-intervention. Findings are in disagreement with the findings of a study done in South Africa by Garfar et al 20 that observed a significant association between participants' age and compliance level.…”
Section: Comparing Association Between Age Of the Patient And Complia...supporting
confidence: 92%
See 1 more Smart Citation
“…The outcome of the present study shows that the age of a patient does not determine their compliance to the treatment regimen, hence health education intervention should be targeted to all the patients in the referral hospital to ensure compliance. The finding corresponds with the observations of Mbuti et al 19 that reported no significant association between age and compliance to treatment regimen after post-intervention. Findings are in disagreement with the findings of a study done in South Africa by Garfar et al 20 that observed a significant association between participants' age and compliance level.…”
Section: Comparing Association Between Age Of the Patient And Complia...supporting
confidence: 92%
“…The present study results showed that health education intervention continues to be a controlling tool towards behavioural change in medication adherence. The finding is in line with a Kenya study by Mbuti et al 16 that showed health education intervention improved adherence to medication regimens. It also agrees with Lee et al 17 that reported greater adherence to the intervention than the control group.…”
Section: Factors That Affect Compliance To Ptb Drug Regimen Among Par...supporting
confidence: 91%